2015
DOI: 10.1038/ncb3207
|View full text |Cite|
|
Sign up to set email alerts
|

NF-κB activation impairs somatic cell reprogramming in ageing

Abstract: Ageing constitutes a critical impediment to somatic cell reprogramming. We have explored the regulatory mechanisms that constitute age-associated barriers, through derivation of induced pluripotent stem cells (iPSCs) from individuals with premature or physiological ageing. We demonstrate that NF-κB activation blocks the generation of iPSCs in ageing. We also show that NF-κB repression occurs during cell reprogramming towards a pluripotent state. Conversely, ageing-associated NF-κB hyperactivation impairs the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
83
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 59 publications
2
83
0
Order By: Relevance
“…4 Accordingly, we have provided evidence for a direct regulation of DOT1L and YY1 genes by NF-kB, and a striking over-expression of DOT1L in NGPS fibroblasts, suggesting that these proteins might be relevant effectors of NF-kB role in cellular reprogramming as well as in NF-kB-driven alterations. 2 Additionally, the administration of a specific DOT1L chemical inhibitor remarkably increased the reprogramming efficiency of NGPS fibroblasts. 2 Furthermore, the parallelism observed between rejuvenation and reprogramming enhancement through NF-kB inhibition suggested that DOT1L could be a novel target for rejuvenation-based approaches (Fig.…”
Section: Reprogramming Aging Through Dot1l Inhibitionmentioning
confidence: 99%
See 4 more Smart Citations
“…4 Accordingly, we have provided evidence for a direct regulation of DOT1L and YY1 genes by NF-kB, and a striking over-expression of DOT1L in NGPS fibroblasts, suggesting that these proteins might be relevant effectors of NF-kB role in cellular reprogramming as well as in NF-kB-driven alterations. 2 Additionally, the administration of a specific DOT1L chemical inhibitor remarkably increased the reprogramming efficiency of NGPS fibroblasts. 2 Furthermore, the parallelism observed between rejuvenation and reprogramming enhancement through NF-kB inhibition suggested that DOT1L could be a novel target for rejuvenation-based approaches (Fig.…”
Section: Reprogramming Aging Through Dot1l Inhibitionmentioning
confidence: 99%
“…2 Additionally, the administration of a specific DOT1L chemical inhibitor remarkably increased the reprogramming efficiency of NGPS fibroblasts. 2 Furthermore, the parallelism observed between rejuvenation and reprogramming enhancement through NF-kB inhibition suggested that DOT1L could be a novel target for rejuvenation-based approaches (Fig. 1).…”
Section: Reprogramming Aging Through Dot1l Inhibitionmentioning
confidence: 99%
See 3 more Smart Citations